Influence of Dietary Oil Content and Conjugated Linoleic Acid (CLA) on Lipid Metabolism Enzyme Activities and Gene Expression in Tissues of Atlantic Salmon (Salmo salar L.) - Kennedy, Sean Robert; Leaver, Michael; Campbell, Patrick; Zheng, Xiaozhong; Dick, James R; Tocher, Douglas R (Lipids, 2006)
The overall objective is to test the hypothesis that conjugated linoleic acid (CLA) has beneficial effects in Atlantic salmon through affecting lipid and fatty acid metabolism. The specific aims of the present study were to determine the effects of CLA on some key pathways of fatty acid metabolism including fatty acid oxidation and highly unsaturated fatty acid (HUFA) synthesis. Salmon smolts were fed diets containing two levels of fish oil (low, ~18% and high, ~34%) containing three levels of CLA (a 1:1 mixture of 9-cis,trans-11 and trans-10,cis-12 at 0, 1 and 2% of diet) for 3 months. The effects of dietary CLA on HUFA synthesis and β-oxidation were measured and the expression of key genes in the fatty acid oxidation and HUFA synthesis pathways, and potentially important transcription factors, peroxisome proliferators activated receptors (PPARs), determined in selected tissues. Liver HUFA synthesis and desaturase gene expression was increased by dietary CLA and decreased by high dietary oil content. Carnitine palmitoyltransferase-I (CPT-I) activity and gene expression were generally increased by CLA in muscle tissues although dietary oil content had relatively little effect. In general CPT-I activity or gene expression was not correlated with β-oxidation. Dietary CLA tended to increase PPARα and β gene expression in both liver and muscle tissues, and PPARγ in liver. In summary, gene expression and activity of the fatty acid pathways were altered in response to dietary CLA and/or oil content, with data suggesting that PPARs are also regulated in response to CLA. Correlations were observed between dietary CLA, liver HUFA synthesis and desaturase gene expression, and liver PPARα expression, and also between dietary CLA, CPT-I expression and activity, and PPARα expression in muscle tissues. In conclusion, this study suggests that dietary CLA has effects on fatty acid metabolism in Atlantic salmon and on PPAR transcription factors. However, further work is required to assess the potential of CLA as a dietary ...